Foreign experiences of food industry development and possibilities of using them - Rajabaliyeva Iroda Alisherovna (THE INNOVATION ECONOMY, 2026)
The article analyzes the foreign experience of food production and the possibilities of their use in Uzbekistan. The system of efficiency indicators of foreign experiences of food industry development was analyzed by dividing it into economic, social, technological and environmental efficiency indicators. Also, by introducing modern equipment and innovative technologies into the activities of food industry enterprises by foreign companies the use of the “resource efficiency coefficient” and “technological innovation level” indicators in increasing the volume and efficiency of product production has been studied.